Evaluation of a design thinking MOOC: A preliminary investigation - Sim, Tze Ying *; Lau, Sian Lun * (2020)
Design thinking courses are commonly conducted in a workshop manner. There are courses delivering design thinking using the massive open online course format. However, the findings on the MOOC platform reveals that the platform lacks interactivity and collaboration between learners. This research proposes additional steps in the evaluation of MOOC content through the assessment submissions and feedback by participants. The additional triangulation of ”assessment and feedback” and evaluation complement the common method of independent review of the content. The two additional methods provide more information on the area that needs to be improved. Other factors like motivation for completion and the effectiveness of the content delivered online will also be discussed. The second focus is to identify the impact of online workshops to support the collaboration and interaction aspects. The research studies the utilization of such features in the MOOC platform. This is followed by future work following this research.